Shari’ah Teachings Towards Civilization: A Blueprint to Addressing Societal Crimes - Bello Ali; Lawan Abdullahi Muhammad; Maunde Muhammad Usman; Abdulmumini Bawuro Manga; Murjanatu Ismail Agwaru (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2026)
Purpose – This study examines how Shari’ah teachings within Islamic civilization provide a comprehensive framework for addressing societal crimes and contemporary social crises. The paper responds to the growing challenges of moral decline, economic inequality, governance failures, and environmental degradation by exploring the relevance of Islamic ethical principles such as tawḥīd (divine unity), ʿadl (justice), raḥmah (compassion), and khilāfah (stewardship). It argues that Islamic civilization offers a timeless model for promoting justice, social harmony, and sustainable development. Design/methods/approach – The study adopts a qualitative and analytical research methodology using a descriptive-analytical design. Data were collected through documentary analysis of the Qur’an, classical Islamic scholarship, and contemporary academic literature. Thematic and content analysis were employed to examine the application of Shari’ah teachings to issues relating to societal crimes, governance, welfare, and environmental sustainability. Findings – The findings reveal that Islamic civilization integrates spiritual, social, economic, and environmental dimensions into a unified moral framework. Shari’ah teachings promote accountability, moderation, equality, and consultation (shūrā) as safeguards against corruption and injustice. Economic institutions such as zakāt, ṣadaqah, and waqf support equitable wealth distribution and social welfare, while Qur’anic environmental ethics discourage wastefulness (isrāf) and corruption (fasād). The study further finds that Islamic principles provide preventive and transformative approaches to societal crimes through moral reform, social responsibility, and ethical governance. Research implications/limitations – The study is limited to qualitative analysis based on documentary sources and does not include empirical fieldwork. Its conclusions are primarily interpretive and focused on Islamic civilizational thought, which may limit broader comparative application. Originality/value – This study contributes to contemporary discourse by positioning Islamic civilization as a holistic framework for crisis management, ethical governance, crime prevention, and environmental stewardship. It highlights the enduring relevance of Shari’ah principles in addressing modern societal challenges while offering a value-based alternative to secular approaches to civilization and development.